Pengaruh Corporate Governance Terhadap Profitabilitas dan Nilai Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) - I Gede Cahyadi Putra; Ida Ayu Ratih Manuari; Ni Kadek Dewi Puspayanti (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2022)
This study aims to examine and obtain empirical evidence of the effect of corporate governance on firm value through profitability in manufacturing companies listed on the Indonesia Stock Exchange. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 - 2020, totaling 195 companies. The sample in this study were 40 companies which were determined based on purposive sampling technique. The analytical technique used is partial least square (PLS). The results show that corporate governance and profitability have a positive and significant effect on firm value. Corporate governance has a positive and significant effect on profitability. Corporate governance has an indirect effect by having a positive and significant influence on firm value through profitability.